2021
DOI: 10.1016/j.jiph.2020.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silver nanoparticles using gum Arabic: Evaluation of its inhibitory action on Streptococcus mutans causing dental caries and endocarditis

Abstract: Background Streptococcus mutans are an oral pathogen that causes dental caries, endocarditis, and systemic dysfunctions, an alternative antibacterial solution from silver nanoparticles (AgNPs) are investigated. Methods AgNPs were synthesized using the ethnobotanical product gum Arabic. It influenced the nanoparticles with medicinal value through their role as capping, stabilizing, or surface-attached components. The biophysical characteristics of the synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 39 publications
5
32
0
1
Order By: Relevance
“…Bacterial growth inhibition was observed at 6.25-100 µg/mL for the two GA-AgNPs for all strains, with an MIC of 6.25 µg/mL, except for GA-AgNPs_0.4g effect in E. coli which had an MIC of 25 µg/mL. The MIC values were consistent with the GA-AgNPs reported by other studies; the NPs had an MIC of 10 µg/mL in S. mutans [67], 11-45 µg/mL in P. aeruginosa [44], 1.625 and 3.25 µg/mL for A. hydrophila and P. aeruginosa, respectively [68]. The results in the current study were further confirmed by the Alamar Blue assay, which quantifies the metabolic activity of cells.…”
Section: Anti-bacterial Activitysupporting
confidence: 88%
See 1 more Smart Citation
“…Bacterial growth inhibition was observed at 6.25-100 µg/mL for the two GA-AgNPs for all strains, with an MIC of 6.25 µg/mL, except for GA-AgNPs_0.4g effect in E. coli which had an MIC of 25 µg/mL. The MIC values were consistent with the GA-AgNPs reported by other studies; the NPs had an MIC of 10 µg/mL in S. mutans [67], 11-45 µg/mL in P. aeruginosa [44], 1.625 and 3.25 µg/mL for A. hydrophila and P. aeruginosa, respectively [68]. The results in the current study were further confirmed by the Alamar Blue assay, which quantifies the metabolic activity of cells.…”
Section: Anti-bacterial Activitysupporting
confidence: 88%
“…The two GA-AgNPs exhibited similar activity against the test bacteria. Similar effects were reported for GA-AgNPs synthesized using other GA species; the GA-AgNPs were potent against oral (Streptococcus mutans) [67] and fish (Aeromonas hydrophila and P. aeruginosa) [68] pathogens.…”
Section: Anti-bacterial Activitysupporting
confidence: 79%
“…The supernatant was stored for the synthesis of AgNPs, which was optimized using the Taguchi method. According to this method, nine experiments were designed based on different factors, including silver nitrate (AgNO 3 ) concentrations (0.3, 0.6, and 0.9 mg/mL), incubation times (48, 72, and 96 h), and incubation temperatures (27,32, and 37 °C). The synthesis process was started by adding 0.5 mL of the bacterial supernatant to the AgNO 3 solution at different concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Among the available MNPs, much attention was given towards the exploitation of the biomedically-related effects of AgNPs, particularly its antimicrobial effects. Silver has a long history in dental application, initially in the form of ionic compounds [78], and recently, in NP formulation [79][80][81]. Many studies have demonstrated the antimicrobial effects of 38% silver diamine fluoride (SDF) in the prevention of caries, where the ionic silver and fluoride served as antimicrobial and remineralization agents, respectively [82,83].…”
Section: Agnps In Dental Therapymentioning
confidence: 99%